Strategies of Handlying Bullying at Private Junior High Schools in Samarinda - Andi Meldayani; Zulkipli Lessy; Yuli Kuswandari (Proceeding International Conference on Religion, Science and Education, 2023)
Bullying is one type of aggressive action that can harm others. The purpose of this study was to investigate teachers’ strategies in dealing with bullying at a private Junior High Schools in Samarinda. This study uses a qualitative type with a phenomenological approach. The subjects of this study involved 6 teachers of the Samarinda Ulu Private Junior High Schools. Data collection techniques of this research were observation, documentation, and interviews. To analyze data, this reserah used data reduction, data exposure, and drawing conclusions. The results of this research showed that 5 schools did not have specific rules regarding handling bullying and 1 school already had rules on bullying even though the rules were still general, but strategies in handling cases/violations that occurred in general had been implemented. There were several stages in dealing with perpetrators and victims of bullying cases. The stages started from giving a warning and giving punishment if the perpetrators did more than once. If they didi it more than 3 timesi the school invited the parents to schools. Finally, the worst punishment was that the school dropped out students. Each case was treated differently according to the type of problem/violation committed by the students.